Penggunaan Media Gambar pada Pembelajaran Ragam Gerak Tari Guel di Kelas V SD Negeri 3 Lut Tawar Aceh Tengah - Aida Fitri; Taat Kurnita Y (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2021)
Media is everything that can be used to convey messages or information in the teaching and learning process to stimulate students' attention and interest in learning. This study aims to describe the use of image media in learning the variety of Guel dance movements in V Grade of SD Negeri 3 Lut Tawar, Central Aceh. This research approach is qualitative with descriptive type—data collection techniques by observation, interviews. Data analysis was carried out by data reduction, presentation, and verification. Based on research data on the use of image media in learning the various movements of the Guel dance in V Grade of SD Negeri 3 Lut Tawar, Central Aceh, the teacher has used image media as a tool to help the learning process of the various movements of the Guel dance to achieve the expected goals. The image media used by the teacher is photographic image media, namely the teacher as an example in photography by making every variety of movements from the Guel dance. There are as many as 50 different movements along with floor patterns and Guel dance rhymes.